The Effects Of Waste Coffee Fermented To Feed Efficiency And Protein Efficiency Ratio (PER) Etawa Crossbreed Goat (PE) - aditya tri pambudi (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2015)
AbstractThe aim of this research was to find out of the effects of waste coffee fermented to feed efficency and protein efficiency ratio (PER) peranakan etawa (PE) goat. This research implemented in Village Balesari ngajum District of Malang. The research was conducted on 9 July-7 September 2015 start of the preparation of the material until the data collection phase. The method used was a laboratory experiment and experiments In-Vivo material used in this study are: goats totaled 9 tail, elephant grass, pollard, fermented feed waste coffee, with treatment P0 with 100% pollard, P1 50 % pollard: KKF 50% and P2 40% pollard : 60% KKF. The results showed that waste skin coffe fermented gave significant (P<0.05) to feed efficiency. The highest feed efficiency were P1 (15.71%). waste skin coffe fermented gave significant (P<0.05) to protein effeciency ratio (PER). The highest protein effeciency ratio (PER) were P1 (0.29). The conclusion that feed effeciency best at the treatment P1 with the value 15.71%, the protein effeciency rasio (PER) best at the treatment P0 with the value 0.29. Keywords : Peranakan Etawa (PE) Goat, Waste Coffee Fermented, Feed Efficiency, Protein effeciency Ratio (PER)